The Effectiveness of Hellotalk App on English Writing, Hanafi-Salwa - Hanafi Wibowo; Salwa Raihani (Lingua, 2019)
The objective of this research is to find out the effectiveness of using HelloTalk app to enhance the writing skills of language learners of the students 10th grade of As-syafi’iyah Islamic Senior High School 02. The type of research use is pre-experimental design (pre-test and post-test one group design) by using t-test with SPSS 22 for windows. Based on the result of research can be proved that there is significant effectiveness of using HelloTalk app in writing skills students 10th grade, in As-syafi’iyah Islamic Senior High School 02. This is shown by the pre-test mean (61,43) and the post-test mean (87,14). The correlation between two variables is 0,414 with sig of 0,028. This shows that the two averages pre-test and post-test is strong and significant.